Written lists as mediating stimuli in the matching-to-sample performances of individuals with mental retardation. - Stromer, R (1998)
Students with mental retardation learned to write lists in order to perform a matching task that they could not do otherwise. After an initial assessment phase, reinforcement was arranged in the computerized tasks to follow selection of the six pictures that were identical to those in the six-picture samples presented. In Study 1, even though the participants wrote a list of the names of the six sample pictures on each trial, read a list, or did both, they often made errors when a brief delay preceded picture selection. In contrast, performance was nearly perfect when a list was written, read, and remained available at the time of picture selection, suggesting that the list served to mediate the delays. Study 2 examined the stimulus control by two- and six-picture samples over the list writing. Early during testing, 1 participant refrained from writing lists on two-picture trials but wrote lists on six-picture trials, thereby maximizing reinforcement and minimizing its delay; the other participant showed this pattern of list writing after supplemental training. The studies suggest methods for establishing a rudimentary repertoire of mediating behavior that has relevance for teaching instruction-following skills in natural settings.